2021
DOI: 10.1155/2021/5015797
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Insulin Secretion and Arterial Stiffness in Essential Hypertension

Abstract: The study aims to explore the relationship between plasma insulin secretion and arterial stiffness in nondiabetic essential hypertensive patients. A total of 730 nondiabetic essential hypertensive patients registered between January 2016 and October 2020 were enrolled. A two-hour oral glucose tolerance test (OGTT) was performed to detect the levels of C-peptide and blood glucose at 0 hours and 2 hours, as well as the difference between C-peptide (Δ C-peptide) and blood glucose (Δ blood glucose) over the same p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…It seems that the absence of C-peptide may effectuate increased cardiovascular risk in T1DM patients. However, in nondiabetic individuals, several studies reported a positive linear association between C-peptide and arterial stiffness markers [ 7 , 22 ]. A higher level of C-peptide had been reported to be correlated with higher risks of subclinical myocardial injury and all-cause and cardiovascular-related mortality [ 8 10 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It seems that the absence of C-peptide may effectuate increased cardiovascular risk in T1DM patients. However, in nondiabetic individuals, several studies reported a positive linear association between C-peptide and arterial stiffness markers [ 7 , 22 ]. A higher level of C-peptide had been reported to be correlated with higher risks of subclinical myocardial injury and all-cause and cardiovascular-related mortality [ 8 10 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…HRs and 95% CIs were derived from a Cox proportional hazard model adjusting for sex, age, smoking status, use of antihypertensive medication, use of lipid-lowering medication, use of antidiabetic medication, BMI, SBP, LDL cholesterol, triglycerides, HbA1c, HOMA-IR, and the interaction between fasting C-peptide and HOMA-IR. BMI body mass index, CI confidence interval, FPG fasting plasma glucose, HbA1c hemoglobin A1c, HOMA-IR homeostasis model assessment of insulin resistance, HR hazard ratio, LDL cholesterol low-density lipoprotein cholesterol, T2DM type 2 diabetes mellitus, 2hPG 2 h plasma glucose C-peptide and arterial stiffness markers [7,22]. A higher level of C-peptide had been reported to be correlated with higher risks of subclinical myocardial injury and allcause and cardiovascular-related mortality [8][9][10]23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Обращает внимание, что в модель ОШ наличия АГ у обоих полов входит С-пептид (ОШ 2,73 у М и ОШ 1,9 у Ж) во взаимосвязи с сосудистой жесткостью (СПВ). Полученные данные подтверждают, что эндогенная секреция С-пептида может играть важную роль в формировании и прогрессировании артериальной жесткости у пациентов с АГ, даже не страдающих диабетом [17,19]. Вместе с тем последние данные свидетельствуют о том, что повышенный уровень продукта расщепления проинсулина С-пептид может выполнять роль медиатора, являясь причиной атерогенеза, способствуя привлечению моноцитов и лимфоцитов в ранние атеросклеротические поражения и индуцируя пролиферацию гладкомышечных клеток сосудов [19].…”
Section: Discussionunclassified
“…In type 2 diabetes, however, insulin levels are often increased at the beginning of the disease (34), and insulin resistance, which characterizes type 2 diabetes, is associated with incident hypertension (35). Insulin resistance and insulin secretion are also associated with increased pulse wave velocity (PWV), a marker of vascular ageing (36,37). However, a causal relationship between insulin and hypertension is uncertain (33,38), and in a study of 596 individuals, insulin levels were not associated with the future development of hypertension (32).…”
Section: Pathophysiologymentioning
confidence: 99%